"Big data" and the "Internet of things", or what accelerates the development of the agro-industrial complex. (May 2019) - Koptilina, D; Bulgakov, A; Aleshina, A
Abstract: The development of agriculture plays a significant role in the economy of each country. The entire agro-industrial complex not only shows the standard of living of the population, but it also forms the financial, resource potential of a particular region. Therefore, the study of different ways to improve the efficiency of management is important. The article is devoted to the analysis and understanding of various manifestations of business intelligence in the agricultural sector, which contribute to the development of this industry, making all the processes taking place in it more productive. Particular attention is paid to the development of new technological devices, which clearly demonstrates the importance of using business intelligence to optimize the functioning of all industries of the national economy. It is shown that innovations regarding information processing methods penetrate all levels of the agro-industrial sector, becoming the object of large investments.